high-density molecular map for ryegrass (Lolium perenne) using AFLP markers - Bert, P.F; Charmet, G; Sourdille, P; Hayward, M.D; Balfourier, F (Theoretical and applied genetics, 1999)
AFLP markers have been successfully employed for the development of a high-density linkage map of ryegrass (Lolium perenne L.) using a progeny set of 95 plants from a testcross involving a doubled-haploid tester. This genetic map covered 930 cM in seven linkage groups and was based on 463 amplified fragment length polymorphism (AFLP) markers using 17 primer pairs, three isozymes and five EST markers. The average density of markers was approximately 1 per 2.0 cM. However, strong clustering of AFLP markers was observed at putative centromeric regions. Around these regions, 272 markers covered about 137 cM whereas the remaining 199 markers covered approximately 793 cM. Most genetic distances between consecutive pairs of markers were smaller than 20 cM except for five gaps on groups A, C, D, F and G. A skeletal map with a uniform distribution of markers can be extracted from this high-density map, and can be applied to detect and map QTLs. We report here the application of AFLP markers to genome mapping, in Lolium as a prelude to quantitative trait locus (QTL) identification for diverse agronomic traits in ryegrass and for marker-assisted plant breeding.